2022
DOI: 10.36552/pjns.v26i3.783
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Outcome for Prolapsed Lumbar Intervertebral Disc Based on Visual Analog Scores

Abstract: Objective:  To determine the surgical Outcome for a prolapsed lumbar intervertebral disc based on a visual analog score. Materials and Methods:  A prospective study was conducted in the Department of Neurosurgery at Jinnah Postgraduate Medical Centre, Karachi. A total of 55 patients were included in the study. Questionnaires were used to collect demographic data, presenting symptoms, and the level of the herniated discs. The patients underwent different surgical interventions and then these patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Early surgical intervention for sciatic pain is more effective than conservative treatment for prolonged period. 13 Ahmed et al reported better results with surgical treatment than conservative management. 14 Standard surgical treatment for protruded disc is excision while there are various methods of excision.…”
Section: Discussionmentioning
confidence: 99%
“…Early surgical intervention for sciatic pain is more effective than conservative treatment for prolonged period. 13 Ahmed et al reported better results with surgical treatment than conservative management. 14 Standard surgical treatment for protruded disc is excision while there are various methods of excision.…”
Section: Discussionmentioning
confidence: 99%